Towards an Online Legal Service Platform: An Approach for Establishing Client-Lawyer Interaction in Bangladesh - Tanvir Ahammad; Md. Delwar Hossain; Md. Mahmudul Hasan (Universitas Pendidikan Indonesia (UPI), 2022)
Bangladesh is still lagging behind many countries in adopting legal technology to reinforce the judicial system’s quality because multiple factors affect the quality of legal service provisioning. One of the main factors is the improper interaction between lawyers and clients on various legal issues. Consequently, clients face difficulties finding appropriate lawyers, estimating the duration and expenses of the case, and sometimes losing money due to excessive legal charges. This paper presents an operational web framework that links lawyers and clients in the context of Bangladesh’s legal services system. The framework comprises several modules with a variety of functionalities, such as creating portfolios of lawyers, filtering and hiring preferred lawyers, getting free legal support, estimating time and amount of legal costs, evaluating the lawyers, and the facility of making a complaint about the inappropriate quality of services. However, most of the functionalities of all modules have been experimented with as a prototype through a web application. The results show the usability and applicability of the framework that establishes a client-lawyer relationship paradigm to improve the quality of the legal services system of Bangladesh.